Asymptomatic malaria parasitaemia and seizure control in children with nodding syndrome; a cross-sectional study. Issue 10 (18th October 2018) - Ogwang, Rodney; Anguzu, Ronald; Akun, Pamela; Ningwa, Albert; Kayongo, Edward; Marsh, Kevin; Newton, Charles R J C; Idro, Richard
Abstract : Objective: Plasmodium falciparum is epileptogenic and in malaria endemic areas, is a leading cause of acute seizures. In these areas, asymptomatic infections are common but considered benign and so, are not treated. The effects of such infections on seizures in patients with epilepsy is unknown. This study examined the relationship between P. falciparum infection and seizure control in children with a unique epilepsy type, the nodding syndrome. Design: This cross-sectional study was nested in an ongoing trial 'Doxycycline for the treatment of nodding syndrome (NCT02850913 )'. We hypothesised that, in patients with epilepsy, infection by P. falciparum, including asymptomatic infections, increases the risk of seizures and impairs seizure control. Setting and participants: Participants were Ugandan children with nodding syndrome, age ≥8 years, receiving sodium valproate. All had standardised testing including documentation of the number of seizures in the past month, a rapid malaria test and if positive, the peripheral blood parasite density. Outcomes: The primary outcome was the number of seizures in the past month (30 days). Results: A total of 164/240 (68%) had malaria. Asymptomatic infections (without fever) were seen in 160/240 (67%) and symptomatic infections in 4/240 (2.7%). In participants without malaria, the median (IQR) number of seizures in the past month was 2.0 (1.0–4.0) and it was 4.0 (2.0–7.5) in participants with malaria, p=0.017. The number of seizures in asymptomatic persons was 3.0 (IQR 2.0–7.3) and 6.0 (IQR 4.0–10.0) in symptomatic individuals, p=0.024. Additionally, in asymptomatic patients, a positive correlation was observed between the parasite density and number of seizures, r=0.33, p = 0.002. Conclusion: In patients with nodding syndrome, both asymptomatic and symptomatic malaria are associated with an increased risk of seizures and poorer seizure control. Similar effects should be examined in other epilepsy disorders. Malaria prevention should be strengthened for these patients and chemotreatment and prevention studies considered to improve seizure control.